The Business Battlecard : Winning Moves for Growing Companies. - O'Dea, Paul (Oak Tree Press, 2013)
Using five simple, but crucial questions, The Business Battlecard helps you craft a winning strategy to grow your company and rally your team. A strategy that will win you the war on several fronts: the battle against competitors, the battle for customers' minds, the battle for investors' wallets, and the battle for employees' hearts ... The book's pledge is: to show you how to devise a clear strategy to grow your business; get your team aligned around it; and then execute it. It gives you simple, practical tools to grow and manage your business.